Bio-Inspired Computing -- Theories and Applications 10th International Conference, BIC-TA 2015 Hefei, China, September 25-28, 2015, Proceedings - Gong, Maoguo; Pan, Linqiang; Song, Tao.; Tang, Ke.; Zhang, Xingyi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the proceedings of the 10th International Conference on Bio-Inspired Computing: Theories and Applications, BIC-TA 2015, held in Hefei, China, in September 2015. The 63 revised full papers presented were carefully reviewed and selected from 182 submissions. The papers deal with the following main topics: evolutionary computing, neural computing, DNA computing, and membrane computing.
Keywords: Computer science; Artificial intelligence; Computer simulation; Computer Science; Artificial Intelligence (incl. Robotics).; Simulation and Modeling; Electronic books